2015
DOI: 10.1159/000380763
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metabolic Syndrome on the Hospitalization Rate of Crohn's Disease Patients Seen at a Tertiary Care Center: A Retrospective Cohort Study

Abstract: Background/Aims: Recent studies suggest that markers of mesenteric inflammation, such as increased adipose tissue, may be associated with poor outcomes in Crohn's disease (CD). This study's hypothesis is that CD patients with metabolic syndrome (MetS) have more CD-related hospitalizations than CD patients without MetS. Methods: We conducted a retrospective cohort study of CD patients seen from 2000 to 2012 at our tertiary care center. We analyzed crude and age-, sex- and duration of CD-adjusted incidence rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
(25 reference statements)
0
18
0
Order By: Relevance
“…In a single-centre retrospective cohort study of 868 patients with Crohn’s disease (19.0% of whom were obese), an increased incidence of IBD-related hospitalization was observed in the 4% of the cohort with metabolic syndrome (defined as >3 of the following features: obesity, diabetes mellitus, hypertension, high levels of circulating triglycerides and low levels of circulating HDL cholesterol), compared with those without metabolic syndrome (incidence rate ratio 1.79, 95% CI 1.06–3.00). However, on evaluating different components of metabolic syndrome, presence of diabetes mellitus, high circulating triglyceride levels and low HDL cholesterol levels, but not obesity, were associated with increased incidence of IBD-related hospitalization 81 . In another retrospective cohort study of 240 patients with Crohn’s disease (12.5% of whom were obese), although obesity was identified as a risk factor for surgery on univariate analysis (OR 2.2, 95% CI 1.0–4.8), it was not an independent predictor of surgery after adjustment for confounding variables.…”
Section: Effect Of Obesity On Ibd Coursementioning
confidence: 92%
“…In a single-centre retrospective cohort study of 868 patients with Crohn’s disease (19.0% of whom were obese), an increased incidence of IBD-related hospitalization was observed in the 4% of the cohort with metabolic syndrome (defined as >3 of the following features: obesity, diabetes mellitus, hypertension, high levels of circulating triglycerides and low levels of circulating HDL cholesterol), compared with those without metabolic syndrome (incidence rate ratio 1.79, 95% CI 1.06–3.00). However, on evaluating different components of metabolic syndrome, presence of diabetes mellitus, high circulating triglyceride levels and low HDL cholesterol levels, but not obesity, were associated with increased incidence of IBD-related hospitalization 81 . In another retrospective cohort study of 240 patients with Crohn’s disease (12.5% of whom were obese), although obesity was identified as a risk factor for surgery on univariate analysis (OR 2.2, 95% CI 1.0–4.8), it was not an independent predictor of surgery after adjustment for confounding variables.…”
Section: Effect Of Obesity On Ibd Coursementioning
confidence: 92%
“…While markers of metabolic syndrome and C-reactive protein were more frequently increased, no association between BMI and need for hospitalization, surgery or medication alterations were noted [140]. Contrarily in CD, the presence of metabolic syndrome increased the risk of hospitalization twofold [141]. In addition a report from France suggested that obese patients with CD had more perianal disease and needed more hospitalizations [142], but in a further study a more mild disease course was found in obese patients with CD [143].…”
Section: Impact Of Obesity On Clinical Outcome Of Ibdmentioning
confidence: 95%
“…Interestingly, also higher abundances of Bacteroides species were found in patients with IBD compared to healthy individuals (112, 113), suggesting that a disturbance of the gut microbial balance in favor of Bacteroides is linked to inflammation of the GI tract. IBD is relatively frequently associated with MetS (114, 115), which adds to the possibility that Bacteroides abundance and disturbances in the inflammatory system are linked. The direction of this relation is currently unclear.…”
Section: Bacteroidesmentioning
confidence: 99%